ANALISIS JARAK DAN KECEPATAN KOMUNIKASI DATA SERIAL ASINKRON MENGGUNAKAN MEDIUM TRANSMISI SINAR LASER - Kurniawan Saputra (Jurnal Informatika, 2011)
Nowadays, many wireless transmission media have been used. Laser can be used as one of data media transmition. Laser can work on the spectrum of 620 nm – 750 nm.  The choosing of electronic component responding time determines data transmission process, both the distance and speed of data transmission. The electronic components chosen in this research are those with responding time measured in ordo nano second and the data communication protocol uses C. In the research, there is a negative correlation between the speed and distance of data transmission. The average farthest distance observed in the research was 313 m with the transmission speed of 9,600 bps. Keywords: protocol, wireless transmission